Arabic English Code-Switching Among Jordanian University Students' Facebook messages: The Syntactic Structure of Noun-Adjective Word Order - Manvender Kaur Sarjit Singh, Marwan Mohammad Al-Thunaibat (International Journal of Advanced Science and Technology, 2020)
Code-switching is a controversial phenomenon and has unresolved questions (Soto et al., 2018). The appearance of universal grammar and the idea of the innateness of language encouraged syntactic theories to explain code-switchingstructure (Boersma and De Bot, 2006).However, the syntactic structure of code-switching is not agreed. There are two different contradictorymodels argue about the syntactic structure of code-switching sentences (Herring, Deuchar, Couto, and Quintanilla, 2010). On the other hand, Arabic-English code-switching is rarely discussed syntactically. Thus, the study focuses on adjective-noun word order among Jordanian university students' Facebook messages. The results of the study found both Matrix language model and minimalist theory are not applicable to govern code-switching in this context. Therefore, future models should find universal principles govern all code-switching contexts.